2022
DOI: 10.1371/journal.pntd.0010702
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability measures of water, sanitation and hygiene interventions in low- and middle-income countries, a systematic review

Abstract: Background Inadequate access to water, sanitation, and hygiene (WASH) is an environmental risk factor for poor health outcomes globally, particularly for children in low- and middle-income countries (LMIC). Despite technological advancements, many interventions aimed at improving WASH access return less than optimal results on long term impact, efficacy and sustainability. Research focus in the ‘WASH sector’ has recently expanded from investigating ‘which interventions work’ to ‘how they are best implemented’.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Acceptability is often central to WASH interventions. Various assessment measures, as described by Hosking et al [ 42 ] can be used to measure acceptability of an intervention. Articles identified in this search utilised validated behavioural frameworks including Trials of Improved Practices (TIPs) used by [ 30 , 36 ], a combination of TIPs and the COM – B framework [ 27 ], the Risks, Attitudes, Norms, Abilities, and Self-Regulation model [ 23 ] and the Integrated Behavioural Model (IBM) for WASH [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acceptability is often central to WASH interventions. Various assessment measures, as described by Hosking et al [ 42 ] can be used to measure acceptability of an intervention. Articles identified in this search utilised validated behavioural frameworks including Trials of Improved Practices (TIPs) used by [ 30 , 36 ], a combination of TIPs and the COM – B framework [ 27 ], the Risks, Attitudes, Norms, Abilities, and Self-Regulation model [ 23 ] and the Integrated Behavioural Model (IBM) for WASH [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frequent disasters such as floods that result in collapsed pits and latrines have deterred ODF communities from rebuilding their latrines, as reported in the Bangladesh study [66]. In addition to the rains, [70] reported that termites attacked the slabs of some pit latrines that were made of wood beams or branches which severely weakened the latrine structure often leading to its collapse. Local pit latrines were not expected to last an entire rainy season.…”
Section: Plos Onementioning
confidence: 97%
“…Social aspects are considered essential and, if not adequately addressed, the failure of the implemented solution is likely to occur [78][79][80]. A number of community, household, and structural factors besides technological factors were found to be associated with better toilet durability, including households with higher socioeconomic status, households with disabled members, living in communities with higher basic sanitation coverage, and having toilets in an area with a shallower water table [62,70]. Several other studies have reported that frequent personal contact with health promoters and accountability over a period of time [81] an enabling environment with market access to latrine products [82][83][84], follow-up monitoring [17,85], social cohesion and social capital among community members [50], effective community leadership and political will [17], access to markets and sanitation materials, and sustainable behavior change [17,50] can lead to increased sustainability of latrines.…”
Section: Plos Onementioning
confidence: 99%
“…Acceptability evaluations are increasingly common across the WASH and broader healthcare sector [16,18]. However, previous acceptability evaluations have lacked a consistent de nition of acceptability and a theoretical underpinning [20]. The local environmental context, including water availability and the frequency of extreme climate events, also affects sustainability of WASH interventions [21,22].…”
Section: Introductionmentioning
confidence: 99%